2019
DOI: 10.1002/icd.2133
|View full text |Cite
|
Sign up to set email alerts
|

The effect of psychological distance on young children's future predictions

Abstract: The current study examined the impact of psychological distance on children's performance on the pretzel task. In this task, children eat pretzels (inducing thirst) and then are asked to reason about future preferences (pretzels or water). Children typically perform poorly on this task, indicating a future preference for water over pretzels, potentially due to conflicting current and future states. Given past work showing that children's future reasoning is more accurate for another person, we asked 90 thirsty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…We predicted that: (1) there will be no age-related improvements in Pretzel task performance in line with past research ( Atance & Meltzoff, 2005 ; Cheke & Clayton, 2019 ; Kramer et al, 2017 ; Mahy et al, 2014 ; Mahy, 2016 ; Mazachowsky, Koktavy, & Mahy, 2019 ), (2) children will perform better on the Pretzel task in the episodic simulation and motivation conditions (selecting water less often as their future preference) compared to the standard thirsty condition, and (3) children will take longer to make their future preference choice in the episodic simulation condition compared to all other conditions (potentially due to engagement in future simulation processes). We also examined children’s explanations for their future choices in an exploratory manner by coding whether children’s explanations focused on their present state, future state, their general preferences, or ‘other’ (if it did not fit into any of the first three categories, including no response).…”
Section: Studysupporting
confidence: 64%
See 1 more Smart Citation
“…We predicted that: (1) there will be no age-related improvements in Pretzel task performance in line with past research ( Atance & Meltzoff, 2005 ; Cheke & Clayton, 2019 ; Kramer et al, 2017 ; Mahy et al, 2014 ; Mahy, 2016 ; Mazachowsky, Koktavy, & Mahy, 2019 ), (2) children will perform better on the Pretzel task in the episodic simulation and motivation conditions (selecting water less often as their future preference) compared to the standard thirsty condition, and (3) children will take longer to make their future preference choice in the episodic simulation condition compared to all other conditions (potentially due to engagement in future simulation processes). We also examined children’s explanations for their future choices in an exploratory manner by coding whether children’s explanations focused on their present state, future state, their general preferences, or ‘other’ (if it did not fit into any of the first three categories, including no response).…”
Section: Studysupporting
confidence: 64%
“…Future research could also explore other manipulations that might also improve children’s EpF in tasks where there is current-future state conflict. For example, Mazachowsky et al (2019) found that having children make decisions for an adult experimenter improved performance on Pretzel task performance (although children were at chance levels) compared to when they made a decision for themselves. Other manipulations, such as having children consider their own past experiences with hunger and thirst, might improve Pretzel task performance (in line with the constructive episodic simulation hypothesis; Schacter & Addis, 2007 ) and help to overcome presentism bias.…”
Section: Discussionmentioning
confidence: 99%
“…Another variable that may be important in explaining younger children's differential responding for self and other is that when children think about their own future, their mental projections are heavily influenced by their current state (e.g., Atance & Meltzoff, 2006;Kramer, Goldfarb, Tashjian, & Lagattuta, 2017;Mahy, 2016;Mazachowsky, Koktavy, & Mahy, 2019). In contrast, this influence is tempered when thinking about another person's future, thus leading to more optimal future-oriented choices (and an other-over-self advantage).…”
Section: Explanations For Other-over-self Advantagementioning
confidence: 99%
“…Importantly, only Prencipe and Zelazo's (2005) study has directly examined the role of making DoG decisions for the self and another person (hence manipulating psychological distance by asking children to take different perspectives). Beyond the domain of DoG, increasing psychological distance by taking the perspective of another person has been shown to increase performance on tasks measuring cognitive control (White & Carlson, 2016), episodic future thinking (Lee & Atance, 2016;Mazachowsky, Koktavy, & Mahy, 2019;Russell, Alexis, & Clayton, 2010), and perseverance (White et al, 2017). Thus, it seems that encouraging children to take the perspective of another person is an effective way to improve children's performance in a number of domains of development.…”
Section: Delay Of Gratification and Psychological Distancementioning
confidence: 99%
“…Similarly in a different experiment, children aged between 3 and 7 years had difficulty overcoming their salient state of thirst, which impaired their future predictions but had more success when predicting for another individual, i.e. the experimenter (Mazachowsky, Koktavy, & Mahy, 2019).…”
Section: Introductionmentioning
confidence: 96%